Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

how do you solve st+3t=6

Sagot :

you will factor out the common factor of t if you are solving for t. you will then divide both sides by (s+3) to make t the subject of the formula. for this question you can only get t in terms of s.
so:
st+3t=6
t(s+3)/(s+3)=6/(s+3)
t=6/(s+3)

if you are required to solve for s then you are going to subtract 3t from both sides. you can factorise 6-3t .you will then divide both sides by t to isolate s.for this question you can only get s in terms of t.so:

st+3t-3t=6-3t
st/t=2(3-t)/t
s=2(3-t)/t